2019
DOI: 10.1080/13574809.2019.1592665
|View full text |Cite
|
Sign up to set email alerts
|

Urban design and public transportation – public spaces, visual proximity and Transit-Oriented Development (TOD)

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Urban design and public transportationpublic spaces, visual proximity and Transit-Oriented Development (TOD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…As generalist model, Spacematrix model has been widely accepted in morphological research and used to analyze urban elements e.g. lots (Bobkova, et al, 2019a;2019b). Todor Stojanovski used the Swedish urban typologies proposed by Carl-Johan Engström and Johan Rådberg to analyze the effect of urban form as neighborhood type on travel (Stojanovski, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As generalist model, Spacematrix model has been widely accepted in morphological research and used to analyze urban elements e.g. lots (Bobkova, et al, 2019a;2019b). Todor Stojanovski used the Swedish urban typologies proposed by Carl-Johan Engström and Johan Rådberg to analyze the effect of urban form as neighborhood type on travel (Stojanovski, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Todor Stojanovski used the Swedish urban typologies proposed by Carl-Johan Engström and Johan Rådberg to analyze the effect of urban form as neighborhood type on travel (Stojanovski, 2018). He used the typology as background for future transformation of Swedish cities (Stojanovski, 2012;2019a) together with a typology of public transportation systems 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The distances between the locations of urban functions and physical features at campuses are a major determinant of peoples' perceived affordances in public spaces. Studies have shown that such linear distances have to be 'short enough' so that human figures become individuals and that it is possible to notice the person's sex, approximate age and activities (Gehl 2011); this can consequently enhance close neighbourly interactions (Canter 1977;Talen and Shah 2007;Stojanovski 2020). Gehl and Svarre (2013) state that human sight allows the detection of peoples' movement at a distance of 100 meters; however, to interact socially and determine details much shorter distances are needed.…”
Section: Location Of Built Environment Featuresmentioning
confidence: 99%
“…Although previous studies already attempted to make use of urban design elements on walking within the station areas in part [11,12,15,[28][29][30][31][32], there was little consideration paid to the characteristics of transformed urban forms, as well as the contribution of various design qualities, with regard to the TOD principles, while cities are confronted with a variety of urban fabrics, and TOD-specific design guides are not on the agenda. Additionally, one single scale (often neighbourhood and occasionally streetscape) was previously addressed-mostly based on the context of the developed world-while the study of the TOD walkability merits multiscale attention.…”
Section: Introductionmentioning
confidence: 99%